PENGARUH OTORITAS KEAGAMAAN DI SEKOLAH ISLAM TERPADU - Solihah Titin Sumanti; Zunidar Zunidar; Hendra Kurniawan; Suryo Adi Sahfutra (Badan Litbang dan Diklat Kementerian Agama RI, 2021)
AbstractThis study aims to show the tendency of urban Muslim communities in the city of Medan in choosing primary schools for children. The number of Islamic schools in Medan City continues to grow. The type of Islamic education that is developing is the Integrated Islamic School (SIT). SIT emerged as a response to the urban Muslim community. Its presence fulfills the wishes of previous Islamic education institutions, such as Islamic boarding schools, madrasas and public schools. The focus of the study looks at the role of the SIT religious authority in shaping teaching so that SIT's ability to compete with schools and Madrasahs affiliated with the NU, Muhammadiyyah, Al-Washliyah, and Al-Ittihadiyah organizations in terms of both curriculum and managerial aspects. The research method used is qualitative naturalistic. The main finding of this research is that the religious authority formed from the learning process at SIT leads to certain groups and ideologies affiliated with the Tarbiyah group. Its religious development indicates that the taste for Islamic education in urban communities leads to SIT which has an integrated curriculum. The managerial system is more modern in use because it is integrated with the existence of quality management in the administrative system that combines the managerial systems of the Ministry of Education and the Ministry of Religion, which are not owned by madrasah or pesantren institutions. The SIT curriculum model is successful in responding to the sociological needs of the urban Muslim community between the needs of religious and general teaching which is also a place to 'entrust' children all day because SIT uses a fullday curriculum model system.AbstrakPenelitian ini bertujuan untuk menunjukkan kecenderungan masyarakat muslim urban di kota Medan dalam memilih sekolah dasar bagi anak-anak. Jumlah sekolah Islam di Kota Medan terus berkembang. Jenis pendidikan Islam yang berkembang yaitu Sekolah Islam Terpadu (SIT). SIT muncul sebagai respon masyarakat muslim urban. Kehadirannya memenuhi keinginan yang tidak dimiliki lembaga pendidikan Islam sebelumnya, seperti pesantren, madrasah, dan sekolah umum. Fokus kajian melihat peran otoritas keberagamaan SIT dalam membentuk pengajaran hingga kemampuan SIT bersaing dengan sekolah dan Madrasah yang berafiliasi pada organisasi NU, Muhammadiyyah, Al-Washliyah, dan Al-Ittihadiyah dari segi kurikulum maupun managerialnya. Metode penelitian yang digunakan adalah kualitatif naturalistik. Temuan utama penelitian adalah otoritas keagamaan yang dibentuk dari proses belajar di SIT mengarah pada kelompok dan ideologi tertentu yang berafiliasi dengan kelompok Tarbiyah. Perkembangan keagamaannya mengindikasikan bahwa selera pendidikan Islam pada masyarakat urban mengarah pada SIT yang memiliki kurikulum integrasi. Sistem managerialnya lebih modern digunakan karena terintegrasi dengan adanya management quality pada sistem administrasi yang menggabungkan sistem managerial Kementerian Pendidikan dan Kementerian Agama, yang tidak dimiliki lembaga madrasah atau pesantren. Model kurikulum SIT berhasil merespon kebutuhan sosiologis masyarakat muslim urban antara kebutuhan pengajaran agama dan umum yang sekaligus menjadi tempat ‘menitipkan’ anak seharian karena SIT menggunakan sistem kurikulum model fullday.